Housing: sector policy paper - World Bank; Word bank (New York: World Bank, 1975)
The book examines the challenges of housing in the developing countries and proffers possible solutions.
usc 24/01/2019
Loans
Keywords: Housing--Finance; Housing policy; Housing; Developing countries